"You, me & TV" — Fighting social isolation of older adults with Facebook, TV and multimodality. Issue 98 (February 2017) - Coelho, José; Rito, Fábio; Duarte, Carlos
Abstract: Social isolation, common in old age, leads to a decrease of both physical and psychological skills and, consequently, to a decreased quality of life and even to a higher mortality risk. Social Network Services, like Facebook, have the potential to increase the amount of online and offline social interactions of older adults. However, because of the huge diversity of characteristics of this user group, the lack of inclusive design principles concerning existing Social Network Services, and the inappropriate ways of interaction available, older adults still resist adopting these services. In this paper we present the "You, me & TV", a television-based multimodal Facebook prototype enhanced with TV shows sharing functionalities, a new feature for sharing printed photos, and multiple interaction modalities – remote control, voice and gestures–. We present three in-depth case studies of the use of this prototype by three older adults aged between 65 and 73 years with distinct levels of experience using Facebook, during a period between 3 and 6 weeks. Results indicate that participants accepted the prototype, rated it highly in terms of usability, and that it improved their interaction with relatives, increasing both online and offline interactions. This was particularly visible for participants that were not Facebook users before the study. We also provide relevant conclusions about the relevancy of photos and how they can easily trigger interactions between older adults and their family, and how using TV as platform for deploying access to Facebook proved to be a contributing factor to their adoption. Finally, we show how adaptation and personalization concepts were perceived and received distinctly among participants. Abstract : Highlights: We report a longitudinal study with a TV enhanced Facebook prototype for older adults. TV, multimodal interaction and photos played an important role on adoption. Functionalities related with sharing TV content and printed photos trigger interactions. Preference for alternative modalities when remote control is difficult to use. Increase of online and offline interaction with family by previous non Facebook users.